Perbandingan Sistem Kepartaian dan Sistem Kepemiluan Indonesia-Amerika Serikat Dalam Penyederhanaan Partai Politik - Maulana, Muhammad Ridho; Gusman, Delfina; Putra, Ilhamdi (Lareh Law Review, 2024)
The party and election system has an impact on the government system with the phenomenon of difficulty in forming opposition groups. So it is important to review the party and election system by comparing it to the system in the United States to find a more efficient format. By using a descriptive-analytical normative juridical method, the results obtained are First, the implementation of the party system in Indonesia and the United States is different, this is driven by the election system, the proportional system encourages Indonesia to adopt a multiparty system, while the district system urges the United States to adopt a two-party system even though there are not only two parties in the country. Second, the reconstruction of the election system can affect the party system as in Duverger's law theory. Many aspects can affect the election process, such as the time of implementation, the number of candidates, and other variables. So by reconstructing the election system, both the system itself and the variables in it can be a solution to the problems of multiparty and presidential in Indonesia. Keywords : Electoral System, Party System, System of Government